Analisis Desentralisasi Fiskal Pada Postur APBD Kota Batam, Provinsi Kepulauan Riau Tahun 2018 - Erinda Alfiani Fauzi; Nike Purnamawati (Jurusan Ilmu Pemerintahan, 2023)
This study focuses on a simple analysis of the public financial posture in Batam City. Fiscal decentralization in Indonesia is carried out by granting broad regional expenditure discretion supported by transfer funding from the center and strengthening local taxing power. Fiscal decentralization is expected to increase the efficiency and effectiveness of governance and public services in the regions. This is due to the proximity of the levels of government providing services to the communities they serve so that local governments understand their local needs and priorities. Furthermore, improving the quality of governance will encourage better access to public services and ultimately boost the regional economy and improve people's welfare.